2006
DOI: 10.1177/0272431606291942
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Nature of Adolescent Friendships

Abstract: Although success in managing evolving peer relationships is linked to critical adolescent outcomes, little is known about the specific factors that lead to success or failure in peer relationship development across adolescence. This longitudinal study examines the role of adolescents' level of ego development as a predictor of the future course of several facets of friendship development in early adolescence. Ego development was assessed in a community sample of adolescents at age 13. Several facets of adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 37 publications
(49 reference statements)
0
7
0
1
Order By: Relevance
“…Other researchers found that youths who were resilient to the negative effects of poverty had greater self-regulatory skills than those who were not resilient in a mixed ethnicity sample (Buckner et al, 2003). In contrast, relatively lower levels of effortful control predicted more conduct problems in Caucasian and Latino children ages 10-14 (Marsh, Allen, Ho, Porter, & McFarland, 2006) and substance use in Latino adolescents (Clark, Donnellan, Robins, & Conger, 2015). Loukas and Roalson (2006) found that youth with lower levels of effortful control experienced more adjustment problems a year later in a sample that was 18% Latino.…”
Section: Effortful Control and Coping In Latino Youthmentioning
confidence: 99%
“…Other researchers found that youths who were resilient to the negative effects of poverty had greater self-regulatory skills than those who were not resilient in a mixed ethnicity sample (Buckner et al, 2003). In contrast, relatively lower levels of effortful control predicted more conduct problems in Caucasian and Latino children ages 10-14 (Marsh, Allen, Ho, Porter, & McFarland, 2006) and substance use in Latino adolescents (Clark, Donnellan, Robins, & Conger, 2015). Loukas and Roalson (2006) found that youth with lower levels of effortful control experienced more adjustment problems a year later in a sample that was 18% Latino.…”
Section: Effortful Control and Coping In Latino Youthmentioning
confidence: 99%
“…In this study, the Internet addiction of adolescents with poor family relationships was also identified at higher levels than for those with good family relationships. Family relationships are an important determinant of children's Internet addiction (Chung et al, 2019;Marsh et al, 2006). Therefore, children and their families should be considered together in projects aimed at preventing Internet addiction.…”
Section: Adolescents' Characteristics Associated With Internet Addictmentioning
confidence: 99%
“…The importance of friendships in early adolescence has been shown in many studies. From childhood through adolescence, friendships become more salient (Buhrmester and Furman 1987 ; Marsh et al 2006 ). Next to that, these relationships deepen, as children spend more time with their friends instead of their parents (Fallon and Bowles 1997 ; Larson et al 1996 ), and the influence of friends becomes greater (Jang 1999 ).…”
Section: Introductionmentioning
confidence: 99%